2019
DOI: 10.1111/ggi.13672
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐Frail Multicomponent Training Intervention project for complexity of biological signals, functional capacity and cognition improvement in pre‐frail older adults: A blinded randomized controlled study protocol

Abstract: Aim Frailty syndrome is related to decreased physiological complexity, functional capacity and cognition. Physical exercise has been suggested to slow down and reverse this syndrome. However, evidence of its effectiveness is not as straightforward as conventionally admitted, as there is a lack of trials with rigorous methodology. The purpose of this study was to describe the Pre‐Frail Multicomponent Training Intervention protocol. Methods Cardiovascular, motor control and neuromuscular systems of pre‐frail old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Several previous studies have shown the relationship between frailty and cognition. Prefrailty is a risk factor for cognitive dysfunction, and cognition tends to decline as frailty increases [ 24 27 ]. A meta-analysis from Bu [ 28 ] summarized that cognitive frailty was found to be a predictor of dementia in older adults living in communities.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown the relationship between frailty and cognition. Prefrailty is a risk factor for cognitive dysfunction, and cognition tends to decline as frailty increases [ 24 27 ]. A meta-analysis from Bu [ 28 ] summarized that cognitive frailty was found to be a predictor of dementia in older adults living in communities.…”
Section: Discussionmentioning
confidence: 99%
“…When necessary, manual support will be provided, which will be diminished gradually. The choice, design, components, and parameters of physical exercise were based on the Otago Exercise Programme (Campbell, Robertson, Gardner, Norton, & Buchner, 1999), Weightbearing Exercise for Better Balance (Sherrington, Lord, & Herbert, 2004), and previous randomized trials from our research group (Ansai et al., 2016; Buto et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…This is a strategy to minimize losses in assessments and to monitor health status. All questions were developed by the authors and carried out according to the purpose of this study and the experiences of previous longitudinal studies from our research group (Andrade et al., 2013; Ansai, Aurichio, Gonçalves, & Rebelatto, 2016; Buto et al., 2019; Santos et al., 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sessions were composed by: a) 10 min of warm-up (light walk); b) 20 min of aerobic exercises; c) 10 min of balance exercise; d) 15 min of resistance exercises; and e) 5 min of cool-down. Details concerning exercise type, intensity, and progression are described in a previous study (27).…”
Section: Intervention Protocolmentioning
confidence: 99%